A novel C2 symmetric chiral stationary phase with N‐[(4‐Methylphenyl)sulfonyl]‐l‐leucine as chiral side chains. Issue 12 (28th May 2020) - Zhu, Junchen; Zhu, Lunan; Wu, Yaling; Cheng, Lingping; Wang, Huiying; Sun, Xiaotong; Shen, Jiawei; Zhou, Yang; Ke, Yanxiong
Abstract: In this study, a series of chiral stationary phases based on N ‐[(4‐methylphenyl)sulfonyl]‐l ‐leucine amide, whose enantiorecognition property has never been studied, were synthesized. Their enantioseparation abilities were chromatographically evaluated by 67 enantiomers. The chiral stationary phase derived from N ‐[(4‐methylphenyl)sulfonyl]‐l ‐leucine showed much better enantioselectivities than that based on N ‐(4‐methylbenzoyl)‐l ‐leucine amide. The construction of C 2 symmetric chiral structure greatly improved the enantiorecognition performance of the stationary phase. The C 2 symmetric chiral stationary phase exhibited superior enantioresolutions to other chiral stationary phases for most of the chiral analytes, especially for the chiral analytes with C 2 symmetric structures. By comparing the enantioseparations of the enantiomers with similar structures, the importance of hydrogen bond interaction, π–π interaction, and steric hindrance on enantiorecognition was elucidated. The enantiorecognition mechanism of trans ‐ N, N ′‐(1, 2‐diphenyl‐1, 2‐ethanediyl)bis‐acetamide, which had an excellent separation factor on the C 2 symmetric chiral stationary phase, was investigated by 1 H‐NMR spectroscopy and 2D 1 H‐ 1 H nuclear overhauser enhancement spectroscopy.